Children's Anthems in the Palestinian Poetry from 1920 to 1948 - Marzouq Badawi Abdallah Al-Badawi (My University, 2004)
It is only by the willing of ALLAH, I have finished this study, the following summary points out the most important remarks and conclusions of the study, these are as follows: 1-Children songs emerged during the Jahilia period, then developed in the Abbasi time, up to the modern time were it developed in a very rapid way in contents and subjects. 2-Poets used to write their children poetry with out dedicating or directing it to children, then scholars following, depending on standards select, illustrate and choose of these and include them in schools books, children use these songs in their daily life so it becomes so popular. 3-National subjects tended to be the most dominant subject on children songs and poetry, this affected their life through depriving them of living their childhood as other children in the world. AS for Palestinian children these songs and poetry were ranked first in popularity. 4-Due to the long and continuous revolution time the Palestinian people is living, and the daily scene of martyrs, the natural result of these conditions is the emerge of martyrs songs and poetry in children songs, and this is not the same in other nations poetry were poets intend to create sense of getting rid of daily worries. 5-Composing songs and poetry for children in the Palestinian culture started as individual and not organized tries for poets, and motivated by the sense of caring for children, and following the footsteps of other poets in other countries. 6-In Palestine we have some poets who showed a lot of care for children poetry, and for this they published their books as (Iskandar Khori) the poet from the city of Beit Jala, his book title was (Singing Child), and (AI-Mathai AI-Manthoum), then came Abu Salma in his collection (Children Songs), and Sheik Mohammed Al- Boustami(The Singer in National Schools Songs), as for the rest of songs these were distributed among many poetry collections. 7-In the thirties and Forties the Palestinian broadcasting station played an important role in the publicity of the children songs, it broadcasted songs for Ibrahaim Touqan, and his sister Fadwa and Issam Hammad and others. 8-It is clear that the literature elements that were clear in the children songs varies from artistic, psychological and language elements, though the songs were not over the standard of the children. 9-There was a variation on the topics of the songs, despite the fact that the national matter was dominating over. 10-The said songs were spreading among both children and old the same, the reason is that these songs were touching the feelings and love of the country, and treating the public suffering of the people, in other words, these songs were playing the role of provoking and motivating the national feelings. 11-It was clear, that despite the easy and fluent language used in the composition of the songs, but, it was rich with ideas and concepts, the lyrical aspect and the music were rich too. 12-The absence of institutions that care for the protection and preservation resulted in the lost of many collections of children songs, so, the presence and fertility and life of the songs were lost too. 13-Through the field study and investigation made on children songs, it i9s clear that the poets who wrote them were teachers or worked in the field of education, and most of them published their own collections. 14-Despite the definition of children songs stated by many scholars, I used the following standard which says( The poet should say that the poem that he has composed is a children song, either he 'published this in a book, a newspaper or any other way, this poem should be easy to sing, using easy and simple language).

علماً بأن عدم مراجعة المدرس للعلامات التي تصله يعني موافقته عليها، وبناء عليه أما وبعد الانتهاء من هذا البحث بعون الله، كان لا بد لي من الإشارة إلى بعضٍ من الملاحظات والنتائج المهمة التي توصلتُ إليها، وهي: 1.إن نشأة النشيد ارتبطت بالعصر الجاهلي، وتطورت في العصر العباسي، وازداد هذا التطور سرعةً وتنوعاً في العصر الحديث. 2.كان بعض الشعراء يكتبون أناشيدهم وقصائدهم البسيطة، دون توجيه أو تخصيص للأطفال، فيأتي بعدهم من يأتي من المهتمين والمختصين، فيختارون منها ما يمكن تقبله لدى الأطفال، وذلك ضمن معايير معروفة، فيلحقونه بالمناهج المدرسية لبعض الصفوف الأساسية، ليصبح فيما بعد نشيداً للأطفال. 3.سيطرة الهم الوطني على أناشيد الأطفال وأشعارهم، مما أدى إلى حرمانهم من ممارسة دورهم الطفولي، كبقية الأطفال في شتى أصقاع الدنيا، فاحتلت الأناشيد الوطنية المرتبة الأولى في أناشيد الأطفال في فلسطين. 4.نتيجة للخصوصية التي تميز بها الشعب الفلسطيني من ثورات متعاقبة، وصور للاستشهاد اليومي، كان أمراً طبيعياً ظهور أناشيد للشهداء في شعر الأطفال، وهذا يُعدُّ خروجاً على طبيعة أناشيد الأطفال بشكل عام، إذ أنها تسعى إلى تخفيف الأعباء والهموم عن نفوس الصغار. 5.إن نظم أناشيد للأطفال في فلسطين، كان محاولات فردية غير منتظمة جاءت نتيجة اهتمام ناظميها بالحركة الأدبية الخاصة بالأطفال، مُقْتَدين بما كان يدور حولهم في البلدان المجاورة. 6.هناك شعراء فلسطينيون أبدوا عناية ملموسة بأناشيد الأطفال، فأصدروا دواوين شعرية خاصة بهم، مثل الشاعر البيتجالي ( اسـكندر الخوري ) في مجموعته ( الطفل المنشد ) و ( المثل المنظوم )، وأبي سلمى في مجموعته ( أغاني الأطفال ) والشيخ محمد البسطامي في مجموعته ( الشادي في الأناشـيد المدرسية الوطنية ) أما بقية الأناشيد فقد كانت متفرقة بين المجموعات الشعرية الخاصة. 7.كان لدار الإذاعة الفلسطينية في الثلاثينيات والأربعينيات من القرن العشرين دورٌ مهمٌ في بث الأناشيد الموجهة للأطفال والتغني بها، من خلال ما كان يقدمه أبو سلمى وإبراهيم طوقان وفدوى طوقان وعصام حماد وغيرهم. 8.يلاحظ أن العناصر الأدبية التي قامت عليها الأناشيد كانت في معظمها تراعي الشروط النفسية والأدبية والفنية واللغوية لأناشيد الأطفال، ولم تكن فوق طاقاتهم الذهنية والوجدانية. 9.تنوع الأغراض الشعرية في أناشيد الأطفال كان ملموساً، على الرغم من بروز النشيد الوطني بشكل لافت للنظر. 10.إن كثيراً من هذه الأناشيد قد تداولها الصغار والكبار على حد سواء، لأنها كانت تلامس الوجدان الإنساني، والجرح الذي يعاني منه المجتمع الفلسطيني، دون النظر إلى الفوارق العمرية، التي تمثل إشباعاً نفسياً ومعنوياً للروح الوطنية المحترمة لدى الجميع. 11.لقد غلب طابع البساطة والسهولة على أكثر الأناشيد، إلى جانب الفكرة الغنية بمضمونها مثلما امتازت بالموسيقا الجذابة والإيقاع الجميل، فكانت في معظمها تتمتع بقدر من الفنية العالية في الصياغة والبناء. 12.إن غياب المؤسسات والجهات الراعية لمثل هذا النوع الفني من شعر الأناشيد، جعلها عرضة للضياع والاندثار، مما أفقدها الحيوية والحضور الدائم. 13.من خلال استقراء أناشيد الأطفال التي درستها، اتضح أن أصحابها كانوا ممن مارسوا في حياتهم التدريس والعمل التربوي، هذا إلى أنهم جميعاً من الشعراء الذين صدرت لأكثرهم دواوين خاصة بهم. 14.على الرغم مما أورده الدارسون من تعريفات عديدة للنشيد، فإنني اتخذت مقياساً اعتمدت عليه، يقوم على كون الناظم قد أشار إلى أن ما نظمه يُعدُّ نشيداً سواءً أكان ذلك في ديوانه أم مكان نشره في الصحف وغيرها، هذا إلى جانب قابليته للغناء والخفة اللغوية والبساطة.
اناشيد الاطفال في الشعر الفلسطيني من سنة 1920-1948